Biomedical Polymers Synthesis and Processing - Damodaran, Vinod B.; Bhatnagar, Divya; Murthy, N. Sanjeeva (SpringerBriefs in Applied Sciences and Technology, 2016)
This book presents a comprehensive review on the various processing and post-processing methodologies for biodegradable polymers. Written by professionals with hands-on experience on polymer processing, this book provides first-hand knowledge of all contemporary processing techniques. The current status and future challenges in the field are described, as well as a framework for designing novel devices for desired applications.